Random Blood Glucose Distribution in Three Different Communities Based Setting: A Pilot Study in Jakarta Area, Indonesia - Ruslialdi, Mochamad A.; Nurrachmayanti, Ardilla; Susanto, Fendy; Susanto, Fendy; Sie, Susana (Pakistan Journal of Nutrition, 2015)
Diabetes is acknowledged as one of the leading causes of death, including Indonesia which ranks 5th for the highest number of diabetic cases in the world (9.1 million cases). This situation might be worsened due to the high number of undiagnosed cases and the increase level of blood glucose serum (hyperglycemia status), specifically in Jakarta which is the capital city of Indonesia and the most populated city within the country. The aim of present study was to assess the prevalence and random blood glucose serum level distribution within three different communities based settings in Jakarta, which are office, healthcare facilities and residential based setting community. The main sample consisted of 1442 subjects who were participated in a cross-sectionally study design. The results showed that prevalence of subjects having random blood glucose serum above 200 mg/dL was 8.9%. The highest prevalence of community having random blood glucose above 200 mg/L was observed in primary health care (13%), followed by residential community (12.9%) and office community (12.5% for media, 1.7% for government; 1.7% for manufacturing and 0.7% for service). While random hyperglycemia status was more prevalent in male population (10.3 vs 8.3%) and oldest age group (0% for <17 year group; 0.8% for 18-27 year group; 3.3% for 28-37 year group; 7.6% for 38-47 year group; 10.6% for 48-57 age group and 12.9% for >58 year group). The creation of integrated intervention strategy to reduce the increasing number of hyperglycemia status should be encouraged. Furthermore, the initiatives created should be the responsibility of all related stakeholders in order to contribute to healthier in Jakarta.